Creative Tourism Development Model Through Natural Dyeing Batik Educational Tourism To Increase Interest In Tourism Visits In The Natural Village Of Malon, Semarang City - Nina Mistriani; Febe Humble Kristanto; Vinka Wahyu Pramesti; Anggun Rina Ardiana; Regina Marsya Maharani; Putri Aulia Hamidah; Atalya Taqwa Setyo Nurani Dewi; Ida Rohmawati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Tourist creative development through batik education tour is one of an effort in conserving culture of Indonesian society, encouraging empowerment of society. One of them is on the Malon Village which develops a creative tourism. This study aims to analyze the development models of creative tourism through natural-colored batik education tour to increase the interest of tourist visits in an effort to enhance the small to medium tourism business to improve the local economy. This study uses qualitative methods, a field observation, interviews, and library studies. The result of this Natural Thematic Malon Village has a privilege in natural dyeing sources from processing or reusing the natural waste (leaves, bamboo, woods and others) in the environment around the village. These things give an impact to waste utilization, and are friendly for the environment as well. In its development this place became a Creative Malon Village model that provides nature-dyeing batik education tour, however there is a number of necessary things that need to be fixed related to the marketing that is narrow. Promotions are more focused on exhibitions at the mall or certain programs, rather than using social media and E-commerce to help the development of creative tourism for the village incomes and the interest of tourist visits. The Pentahelix involvement on developing business involving the role of SMEs and local village government.